2015
DOI: 10.3390/s150715888
|View full text |Cite
|
Sign up to set email alerts
|

Foot Pose Estimation Using an Inertial Sensor Unit and Two Distance Sensors

Abstract: There are many inertial sensor-based foot pose estimation algorithms. In this paper, we present a methodology to improve the accuracy of foot pose estimation using two low-cost distance sensors (VL6180) in addition to an inertial sensor unit. The distance sensor is a time-of-flight range finder and can measure distance up to 20 cm. A Kalman filter with 21 states is proposed to estimate both the calibration parameter (relative pose of distance sensors with respect to the inertial sensor unit) and foot pose. Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Then, is the position of point in the IMU coordinate frame. The height of the IMU is calculated as [ 21 ]: and can be rewritten as: where is the measurement and is a measurement noise at the time : and is: …”
Section: Virtual Blind Cane Operationmentioning
confidence: 99%
“…Then, is the position of point in the IMU coordinate frame. The height of the IMU is calculated as [ 21 ]: and can be rewritten as: where is the measurement and is a measurement noise at the time : and is: …”
Section: Virtual Blind Cane Operationmentioning
confidence: 99%
“…Data were recorded on one subject while walking. Finally, Duong et al [ 28 ] presented an algorithm for the estimation of a single foot pose by fusing data provided by two IR-ToF sensors and an IMU during different motor tasks (walking, dancing steps, jumping and kicking a ball) performed by a single subject. Unfortunately, none of the abovementioned studies, with the exception of [ 18 ], reported the errors associated with the distance estimated by the specific proximity sensor employed under static and dynamic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This is the main idea of ZUPT and ZARU. We use a multi-condition algorithm to detect steps using accelerometer and gyroscope readings (Feliz et al, 2009;Won et al, 2004). According to gravity acceleration, the magnitude of the acceleration a k has to be found between two thresholds.…”
Section: Step Detectionmentioning
confidence: 99%
“…Another solution is to combine inertial sensors with distance measurement sensors. In Duong and Suh (2015) the distance sensor measures the distance by measuring the time of flight of infrared light. This sensor is most often used as a proximity sensor in smartphones.…”
Section: Introductionmentioning
confidence: 99%